The Prevalence of Anti-Rubella Antibodies in Pregnant Women of Turkey, Results of 94508 Patients in a Tertiary Referral Center - Sert, Umit Yasemin; Ozgu-Erdinc, A. Seval; Saygan, Sibel; Engin-Ustun, Yaprak (Zeitschrift für Geburtshilfe und Neonatologie, 2019)
Aim To determine the seroprevalence of rubella in a tertiary referral center inAnkara,Turkey.Materials and methods A retrospective, cross-sectional study was performed from 2008 to 2017 at the outpatient clinic of Zekai Tahir Burak Women Health Care, Training and Research Hospital in Ankara, Turkey. The study included 94508 pregnant women and the patients were evaluated in terms of IgG and IgM status, IgG avidity and amniotic fluid PCR testing if needed.Results Seropositivity for anti-rubella IgG and IgM were 89% and 0.19% respectively. 175 patients with IgM positivity were tested by avidity test, 114 patients were found to have high avidity and 57 patients with low avidity. 4 patients have accepted PCR testing and no positive result was found.Conclusion In our sample of Turkish population, the rate of rubella IgG seropositivity was high suggesting that routine national vaccination programme for rubella is successful. Screening and vaccination of childbearing aged women and updating the national vaccination policy would be effective for the periodic decreases in the immunity.
Keywords: Rubella; screening; antenatal; pregnancy